Sound field “linha de Quimbanda” of “Terreiro de Umbanda Reino de Luz”: sound and prejudice (Per Musi, 2013)
The Umbanda is an afro-Brazilian religion and, as it is practiced in the Reino de Luz, is essentially sonorous. This religion suffers much prejudice for being related, for some not adepts, to the practical of the “evil”, cultured black magic and to the devil. In this work, I consider to analyze the umbandistaCosmo vision through the practical of “Pontos Cantados” (typical religious songs), through sonorous practices, through the speeches of the participants of aspecific religious group, called “Terreiro de UmbandaReino de Luz”, working with its main points of attrition in opposite of the visions of the common sense. I believe that through the analysis of the sounds of this environment, allied to the speeches of the members of the “terreira” (the religious group”, let us better understand the existing preconceptions in relation to this religion and its attempts of adaptation for better social acceptance.